Pest categorisation of Coleosporium asterum, C. montanum and C. solidaginis - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A Navas‐Cortes; et al. (EFSA Journal)
Abstract The EFSA Plant Health Panel performed a pest categorisation of Coleosporium asterum (Dietel) Sydow & P. Sydow, Coleosporium montanum (Arthur & F. Kern) and Coleosporium solidaginis (Schwein.) Thüm, three basidiomycete fungi belonging to the family Coleosporiaceae, causing rust diseases on Pinus spp. (aecial hosts) and on Asteraceae (telial hosts). Coleosporium asterum was described on Aster spp. in Japan and has been reported from China, Korea, France and Portugal. Coleosporium montanum is native to North America, has been introduced to Asia and has been reported from Austria on Symphyotrichum spp. Coleosporium solidaginis has been reported on Solidago spp. from North America, Asia and Europe (Switzerland and Germany). There is a key uncertainty about these reported distributions, due to the until recently accepted synonymy between these fungi and the lack of molecular studies. The pathogens are not listed in Annex II of Commission Implementing Regulation (EU) 2019/2072, an implementing act of Regulation (EU) 2016/2031, or in any emergency plant health legislation. There are no reports of interceptions of C. asterum, C. montanum or C. solidaginis in the EU. The pathogens can further enter into, establish in and spread within the EU via host plants for planting, other than seeds and host plant parts (e.g. cut flowers, foliage, branches), other than fruits. Entry into and spread within the EU may also occur by natural means. Host availability and climate suitability in the EU are favourable for the establishment of the pathogens in areas where host plants in the Asteraceae and Pinaceae co‐exist. Impacts can be expected on both aecial and telial hosts. Phytosanitary measures are available to reduce the risk of further introduction and spread of the three pathogens in the EU. Coleosporium asterum, C. montanum and C. solidaginis satisfy the criteria that are within the remit of EFSA to assess for these species to be regarded as Union quarantine pests, but a key uncertainty exists about their EU distribution.